2002
DOI: 10.1097/00005768-200205000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Decreased taurine concentration in skeletal muscles after exercise for various durations

Abstract: Taurine concentration was decreased in all skeletal muscles after exercise, regardless of the duration. Moreover, this decrease was specific to fast-twitch dominant fibers. However, under these conditions, the plasma taurine concentration remained unchanged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 21 publications
2
48
1
Order By: Relevance
“…The taurine treatment restored MT of exercised dystrophic muscle, in line its high effectiveness when applied in vitro and likely in relation to a direct stimulation of the Ca 2ϩ ATPase pump of sarcoplasmic reticulum (Huxtable, 1992;De Luca et al, 2001). Conditions of muscle taurine depletion are in fact characterized by negative MT and a difficulty of dystrophic muscle to retain adequate amounts of the amino acid has been documented and can be even worsened by exercise (De Luca et al, 1996McIntosh et al, 1998;Matsuzaki et al, 2002). Similarly, PDN was jpet.aspetjournals.org very effective on MT, corresponding to its ability in vitro to decrease cytosolic Ca 2ϩ levels of dystrophic myotubes .…”
Section: Experimental Conditions Drugs In Vitromentioning
confidence: 66%
“…The taurine treatment restored MT of exercised dystrophic muscle, in line its high effectiveness when applied in vitro and likely in relation to a direct stimulation of the Ca 2ϩ ATPase pump of sarcoplasmic reticulum (Huxtable, 1992;De Luca et al, 2001). Conditions of muscle taurine depletion are in fact characterized by negative MT and a difficulty of dystrophic muscle to retain adequate amounts of the amino acid has been documented and can be even worsened by exercise (De Luca et al, 1996McIntosh et al, 1998;Matsuzaki et al, 2002). Similarly, PDN was jpet.aspetjournals.org very effective on MT, corresponding to its ability in vitro to decrease cytosolic Ca 2ϩ levels of dystrophic myotubes .…”
Section: Experimental Conditions Drugs In Vitromentioning
confidence: 66%
“…Matsuzaki et al 31) showed that treadmill exercise to exhaustion decreased taurine levels in the plantaris, gastrocnemius, and extensor digitorum longus muscles in rats; and such exhaustive exercise-induced decreases in muscle taurine levels have been confirmed in other studies 32,33) . On the other hand, we did not find changes in taurine levels in the plantaris or gastrocnemius muscle in rats that had exercised to exhaustion 34) .…”
Section: B) Taurinementioning
confidence: 81%
“…It was shown that prolonged exercise decreased muscle taurine levels in rats [31][32][33] , but the significance of this decrease remains unclear. In humans, muscle taurine levels were unaltered by a 1-h cycle ergometer exercise with a load of approximately 70% V ・ O2max 19) , a cycle ergometer exercise with a load of 75% V ・ O2max for 1 h, a cycle ergometer exercise at maximal work rate for 20 min 20) , and a 2-h cycle ergometer exercise with a load of 60% V ・ O2max 44) .…”
Section: D) Taurinementioning
confidence: 99%
“…A reduction in skeletal muscle taurine content following prolonged muscle stimulation has 394 previously been established in vitro Matsuzaki et al 2002). Chronic 395 supplementation has been shown to significantly increase muscle taurine concentration resulting in 396 increased muscle force production and partially counteracting the effect of intramuscular taurine 397 depletion that occurs during fatigue (Goodman et concentration (Askew, 1997).…”
Section: The Effect Of Physiological Concentrations Of Taurine and Camentioning
confidence: 99%
“…Reducing the intracellular concentration of taurine has commonly been shown 67 to result in a reduction in skeletal muscle function, primarily resulting in a decrease in muscle force 68 production (Hamilton et al 2006). Evidence is also presented to suggest that depletion of muscular 69 taurine occurs during prolonged muscle activation ; Matsuzaki et al 2002), therefore 70 suggesting a link between fatigue and muscular taurine concentration. 71…”
Section: Introduction 51mentioning
confidence: 99%